Weight Gain Among Cancer Patients Receiving Chemotherapy—Facts and Numbers - Muhammad Shahzeb Khan; Javed Butler; Markus Anker (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Cachexia affects up to 60% of patients with lung cancer, with its prevalence rising up to 80% in advanced stages of disease. In approximately 20% of cases, it is the primary cause of mortality. Five studies, including a total of 4467 patients, across range of cancer types reported data on weight gain in cancer patients undergoing chemotherapy. Across all five studies, an average of 18.3% of patients experienced weight gain > 5% (816 out of 4467 patients). The frequency of weight gain > 5% was highest among breast cancer patients, 18.9% in Pedersini et al (n = 169) and 33.0% in Sella et al (n = 687). In NSCLC patients, weight gain was reported in 18.3% in patients in Patel et al (n = 2301) and 11.7% in Roeland et al (n = 1030). In contrast, colorectal cancer patients showed only 5.7% of weight gain > 5% (Zutphen et al, n = 280). Additionally, weight loss > 5% was reported in 15.1% of breast cancer patients and 28.3% of colorectal cancer patients. Despite weight loss being quantified as a common endpoint in clinical trials focused on cancer cachexia, there is limited data on the impact of weight gain as a marker of a positive outcome among cancer patients. Studies have shown that weight gain of more than 5% within 3 months in NSCLC patients can be associated with improvement in overall survival (OS) and progression‐free survival (PFS) scores. In this post hoc analysis by Roeland et al., the authors defined different percentage cut‐off values for maximum weight gain among patients with non–small cell lung cancer within 3 months of starting platinum‐based chemotherapy. Among all categories, namely, weight gain > 0%, > 2.5% and > 5%, a significant benefit in overall and progression‐free survival was seen and was comparable among all groups. These findings highlight the clinical significance of incorporating strategies that encourage weight gain and to prevent weight loss at the least among cancer patients. Along with further delving into the prognostic value of weight gain and developing methods to encourage this response among cancer patients, future studies should use standardized assessment tools to identify weight gain that could be attributed to underlying pathologic processes such as oedema and congestion. We also suggest that monitoring and reporting of weight changes should be done in all cancer trials.